The Impact of Workplace Spirituality on Educational Staff’s Knowledge Sharing Intentions at Private Universities: A Mediation-Moderation Model - Wijayanti, Ariyani Wahyu; Harsono, Mugi; Riani, Asri Laksmi; Suyono, Joko (International Review of Management and Marketing, 2024)
This study aims to examine the impact of spirituality in the workplace on knowledge-sharing intention, with trust as the mediating variable and gender as the moderating variable. The sample consisted of 249 education personnel from private universities in Central Java selected through convenience sampling. Hypothesis testing in this study was conducted using the PLS-SEM analysis tool. The results showed that spirituality in the workplace significantly affects knowledge-sharing intention. Furthermore, the findings show that trust mediates the effect of workplace spirituality on knowledge-sharing intention, and gender moderates the effect of workplace spirituality on knowledge-sharing intention.